Ultrasound elastography in patients with fatty liver disease - Silva,Luiza de Campos Moreira da (2020)
Abstract Hepatic steatosis, or fatty liver disease, occurs due to the accumulation of lipids in hepatocytes. When it becomes chronic, lobular inflammation develops and the disease can evolve to hepatic fibrosis, liver cirrhosis, or hepatocellular carcinoma. Early diagnosis is desirable because patients diagnosed in the early stage of the disease respond better to treatment. In the early stages of fatty liver disease, the physical examination is often unremarkable. Fatty liver disease and hepatic fibrosis can be diagnosed and monitored through laboratory tests, imaging, and biopsy. Among the imaging methods, ultrasound stands out as an effective means of diagnosing and following patients with liver disease. Ultrasound used in conjunction with elastography (ultrasound elastography) has recently shown great utility in the follow-up of such patients. Ultrasound elastography studies the degree of deformation (stiffness) of an organ or lesion, so that when there is hardening, fibrosis, or cirrhosis of the liver, those alterations are well demonstrated. In this review article, we discuss the application of the different types of ultrasound elastography for liver studies: transient elastography, point shear wave elastography, and two-dimensional shear wave elastography. Although magnetic resonance elastography may also be used in the analysis of liver fibrosis, it will not be addressed in this article.